Strategic Human Capital Management for Improving Staff Competencies: A Case Study of Universitas Padjadjaran’s Effort to Increase International University Ranking - Arief, Denden Firman; Sushandoyo, Dedy (Universitas Padjadjaran, 2025)
Internationalization is a strategic priority for universities seeking to strengthen their global standing, yet key research gaps persist. Existing studies predominantly focus on academic staff, policy, governance, or leadership, while the operational role of non-academic staff remains underexplored. Research on administrative capacity rarely integrates behavioral competency frameworks or aligns findings with strategic human capital management (SHCM). Systematic models such as the iceberg model are also seldom applied. Empirical evidence from Indonesian universities is particularly limited, especially studies combining competency gap analysis with strategic human capital formulation. This reveals a clear gap in linking non-academic staff readiness to internationalization goals through a competency-based approach. Addressing this gap, this study examines the readiness of non-academic staff at Universitas Padjadjaran, which targets a QS Top 300 ranking by 2029. Using a sequential explanatory mixed-methods design, a validated 72-item survey of 113 staff members was complemented by follow-up interviews. Findings indicate strong behavioral readiness but gaps in operational competencies, suggesting that constraints are primarily organizational. A strategic human capital management roadmap is therefore proposed to align HR practices with internationalization objectives.